2015
DOI: 10.1089/jwh.2014.4772
|View full text |Cite
|
Sign up to set email alerts
|

Limited Adoption of Current Guidelines for Clinical Breast Examination by Primary Care Physician Educators

Abstract: A majority of physician responders highly involved in education of students and residents continue to practice methods of CBE that do not reflect the current guidelines. Faculty development and training on updated CBE practices may accelerate adoption of guideline-recommended care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Data support the performance of cbe using the vertical strip method instead of the circular ("clock") pattern 44,45 . In addition, the use of 3 fingers, of 3 distinct pressure levels, of a visual examination of the breast, and of an axillary examination should be encouraged 46 . Nevertheless, some authors argue that, despite all efforts at improvement, cbe will still be limited with respect to the minimal lesion size detectable 47 ; however, the Munich Field Study showed that, compared with no early detection, cbe and bse seemed to favourably affect the stage of cancers being detected 48 .…”
Section: Figurementioning
confidence: 99%
“…Data support the performance of cbe using the vertical strip method instead of the circular ("clock") pattern 44,45 . In addition, the use of 3 fingers, of 3 distinct pressure levels, of a visual examination of the breast, and of an axillary examination should be encouraged 46 . Nevertheless, some authors argue that, despite all efforts at improvement, cbe will still be limited with respect to the minimal lesion size detectable 47 ; however, the Munich Field Study showed that, compared with no early detection, cbe and bse seemed to favourably affect the stage of cancers being detected 48 .…”
Section: Figurementioning
confidence: 99%
“…As methods similar to these published studies remain in their infancy, we believe our developed standardized curriculum could serve as a blue print for how trainees could be effectively taught to maintain or improve upon examination techniques. In addition to a possible curriculum for residents, research shows that staff physicians use continuing medical education events (CME) as opportunities to learn and improve upon medical knowledge and skills (3). Similar to resident physicians, staff could be exposed to an abbreviated curriculum at CME events to maintain and improve upon their physical exam skills.…”
Section: Discussionmentioning
confidence: 99%
“…While recognized as essential in patient work up, major deficiencies in performance of physical examination skills from the medical student to the staff physician level have been identified (1). Two, recent studies found that staff physicians do not follow national guidelines for the clinical breast examination (CBE) (2, 3). For example, recent work relating to the CBE found that disregarding national guidelines can result in unacceptable mass detection rates (2).…”
Section: Introductionmentioning
confidence: 99%